Sustainable Murabahah Financing in Improving Members Welfare at BMT Insan Sejahtera Karanganyar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to (1) explain the murabahah financing system at BMT Insan Sejahtera, (2) SWOT analysis of the development of BMT Insan Sejahtera, (3) MUI fatwa regarding usury-free murabahah financing. This study uses a qualitative descriptive method. With primary and secondary data types. Data triangulation is carried out using the interview method. The results shown in the study (1) financing at BMT Insan Sejatera, present changes to the welfare of members. Based on the conclusions of the members, BMT has had a positive impact on increasing business and welfare. With amount based on murabahah financing as of January 1, 2024, to October 23, 2024, it is said to be Rp. 2,390,914,753.00 as many as 272 members, (2) The location of the current financing in the first quadrant (positive, positive) is a profitable position, which supports the implementation of an aggressive strategy (3) And that the installment payment period for murabahah financing at BMT Insan Sejatera does not affect the total price of the goods that have been agreed upon. This proves that the murabahah financing practice at BMT Insan Sejahtera does not contain usury.